2019
DOI: 10.1016/j.celrep.2019.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Metabolic Reprogramming Is an Early Indicator of CD8+ T Cell Dysfunction during Chronic Mycobacterium tuberculosis Infection

Abstract: SummaryThe immunometabolic mechanisms underlying suboptimal T cell immunity in tuberculosis remain undefined. Here, we examine how chronic Mycobacterium tuberculosis (Mtb) and M. bovis BCG infections rewire metabolic circuits and alter effector functions in lung CD8+ T cells. As Mtb infection progresses, mitochondrial metabolism deteriorates in CD8+ T cells, resulting in an increased dependency on glycolysis that potentiates inflammatory cytokine production. Over time, these cells develop bioenergetic deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 57 publications
7
51
2
1
Order By: Relevance
“…We therefore, reasoned that changes in peripheral blood T cell metabolism reflect the waxing and waning of inflammation in response to persistent antigen stimulation, which was normalized by metformin treatment 39−41 . These data are consistent with similar studies and suggest that the beneficial effects of metformin treatment were not due to the restoration of normal systemic glucose metabolism, but rather a direct immunomodulatory effect on immune cells responding to Mtb infection 24,42 . In addition to similar work done in TB, non-TB studies also show that metformin treatment dampens inflammation and limits tissue destruction in a variety of communicable and non-communicable diseases by limiting the differentiation and pro-inflammatory potential of T lymphocytes 28,29 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We therefore, reasoned that changes in peripheral blood T cell metabolism reflect the waxing and waning of inflammation in response to persistent antigen stimulation, which was normalized by metformin treatment 39−41 . These data are consistent with similar studies and suggest that the beneficial effects of metformin treatment were not due to the restoration of normal systemic glucose metabolism, but rather a direct immunomodulatory effect on immune cells responding to Mtb infection 24,42 . In addition to similar work done in TB, non-TB studies also show that metformin treatment dampens inflammation and limits tissue destruction in a variety of communicable and non-communicable diseases by limiting the differentiation and pro-inflammatory potential of T lymphocytes 28,29 .…”
Section: Discussionsupporting
confidence: 91%
“…In addition to its anti-glycemic effects, metformin has also been widely studied as an immunomodulatory drug for the treatment of various other communicable and non-communicable diseases 14 , with observed clinical improvement in patients with cancer, a variety of chronic bacterial and viral infections as well as autoimmune diseases such as systemic lupus erythematosus (SLE) [15][16][17][18][19][20] . Although the exact mechanisms of action have not been determined, metformin has been shown to have a direct effect on immune cell metabolism, which is linked to T lymphocyte differentiation, function, and survival [21][22][23][24][25][26] . This suggests that in addition to normalizing systemic glucose metabolic derangements caused by chronic inflammation, metformin may also modulate the function of immune cells that are important in the protection and pathogenesis of TB.…”
mentioning
confidence: 99%
“…In conclusion the data presented here show that metformin shifts CD8 + T cell metabolism, leading to the expansion of a memory-like CD8 + CXCR3 + phenotype with functional properties that contribute to host control of Mtb infection and disease. Our findings are in line with evidence that metabolic reprograming by metformin reverses CD8 + T cell dysfunction during chronic Mtb infection 66 . Our current and previously reported studies show that metformin ameliorates TB immune pathology, while others reported that it reverses established pulmonary fibrosis in the bleomycin model.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, pyruvate kinase M2 forms a complex with hypoxia-inducible factor-1α (HIF-1α) to promote IL-1β expression and it also phosphorylates STAT3 to boost IL-6 and IL-1β expression (20). More recently, we have demonstrated that Mtb infection of human monocyte-derived macrophages depresses both glycolysis and OXPHOS of the infected macrophage (21) and that Mtb infection leads to a progressive decline in metabolic health of effector T cells (22), suggesting that Mtb rewires host immunometabolism to establish disease.…”
Section: Significancementioning
confidence: 99%
“…4 P, Q, T, and U). We tested this hypothesis by infecting macrophages from CSE −/− and WT mice with Mtb, performing transcriptomic analysis on the RNA isolated from the macrophages, and measuring the rates of glycolysis and mitochondrial respiration using an XF96 Extracellular Flux Analyzer (Agilent), previously adapted by us (21,22,31).…”
Section: Excessive H 2 S Production Stimulated By Mtb Infection Inhibitsmentioning
confidence: 99%